2012
DOI: 10.1049/iet-com.2012.0305
|View full text |Cite
|
Sign up to set email alerts
|

Code acquisition of random optical codes in optical code-division multiple-access

Abstract: In this study, the authors present a technique for code acquisition in optical code-division multiple-access systems using the recently introduced random optical codes. In these systems, the communication is divided in two parts: a synchronisation process and the data transmission. The main target of the study is to describe and analyse the new algorithm of synchronisation using Markov processes. Once described the code acquisition technique and established an estimation for the probability of false alarm (FA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Several asynchronous multiple access schemes were proposed for VLC [10][11][12][13][14][15][16]. For the system in [10] with N transmitters, each transmitter is allocated a unique codeword of length 2 N and a receiver can completely eliminate multiple access interference (MAI) and decode the transmitted data.…”
Section: A Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Several asynchronous multiple access schemes were proposed for VLC [10][11][12][13][14][15][16]. For the system in [10] with N transmitters, each transmitter is allocated a unique codeword of length 2 N and a receiver can completely eliminate multiple access interference (MAI) and decode the transmitted data.…”
Section: A Related Workmentioning
confidence: 99%
“…For N transmitters, a code length greater than 10N is required for each user, while the preamble sequence length needs to be greater than or equal to 30N [14]. Thus, the system throughput is less than or equal to 1 40 bits/chip, which is relatively low.…”
Section: A Related Workmentioning
confidence: 99%
“…From [5], we can see that the optimum weight for codes with length L ≤ 150 is w = 3 for (1/3) L ≤ s ≤ (1/2) L . Moreover, from [5, 6] a tight upper bound for error bit probability P e of the new proposed scheme can be inferred: Pe12sfalse∑i=0s)(si1)(1thinmathspacewLiwfalse(E+1false)Note that the previous P e estimation only depends on the number s of simultaneous users, the parameters of the code L and w and the number E of code extensions. From (1), it is found that error probabilities of approximately or below 10 − 3 can be obtained for E ≥ 2 when s ≤ (2/5) L .…”
Section: System Descriptionmentioning
confidence: 99%
“…However, from [5] we can see that a bit‐error rate (BER) below 10 − 4 requires code lengths L > 10 × s , where s is the number of simultaneous users and L is the number of slots (chips), in which the bit‐transmission interval is divided. Moreover, effective synchronisation preambles must last m × L chips, with m ≥ 3 [6]. Therefore, a large number s of users requires a large L with an increasing synchronisation complexity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation